Isyarat Sains Tentang Air Dalam Al-Qur’an - Sasa Sunarsa (Jurnal Naratas, 2018)
The Qur'an is not a science book but there are many cues about science in Qur'an. It’s newly discovered its secrets based on scientists research  after centuries since demise of Qur'an. One of them is related to water. Water is known one of main themes in life of living.  The word “water” (al-ma`) mentioned in Holy Qur'an and its various forms was founded more than sixty times. One of its topics closely related to science about the water cycle described by Allah in several verses. One of them in Surah An-Nuur/ 24: 43. In this verse describe the stage process and formation of rain water in an appropriate/ logical (scientific) sequence. Thus, the Qur'an provides most correct explanation of this phenomenon of rain with facts to people thousands of years before being discovered and explained by modern science.Kata kunci: Al-Quran; Islam; isyarat sains; air; hujan.